2019
DOI: 10.1007/s11548-019-01918-0
|View full text |Cite
|
Sign up to set email alerts
|

Wearable technology-based metrics for predicting operator performance during cardiac catheterisation

Abstract: IntroductionUnobtrusive metrics that can auto-assess performance during clinical procedures are of value. Three approaches to deriving wearable technology-based metrics are explored: (1) eye tracking, (2) psychophysiological measurements [e.g. electrodermal activity (EDA)] and (3) arm and hand movement via accelerometry. We also measure attentional capacity by tasking the operator with an additional task to track an unrelated object during the procedure.MethodsTwo aspects of performance are measured: (1) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This indicates that they were better able to cope with the stress (Clifford et al, 2020). Currie et al (2019) worked with a similar approach. Their virtual training environment is focused on a high-fidelity surgical procedure.…”
Section: Simulator Trainingmentioning
confidence: 80%
“…This indicates that they were better able to cope with the stress (Clifford et al, 2020). Currie et al (2019) worked with a similar approach. Their virtual training environment is focused on a high-fidelity surgical procedure.…”
Section: Simulator Trainingmentioning
confidence: 80%
“…OSATS and GEARS) [26,28] and provide the trainee with objective, transparent and explicit feedback which is derived from a consensus of expert senior surgeons [11][12][13]15,17]. In contrast to hand/tool 'efficiency' measures these types of performance metrics will also underpin and bolster the development of effective virtual reality simulation and machine learning [20,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Observations of gaze direction, blink frequency, pupil size and dwell time are recognized means of examining attention and cognitive stress [29]. Based on such data Richstone et al were able to distinguish unequivocally between beginners and experts in surgical laparoscopy [30], but for endovascular cardiac interventions, Currie et al found hardly any differences [31]. The assumption that experts would turn their gaze less often away from the X-ray screen could therefore not be confirmed by them.…”
Section: Discussionmentioning
confidence: 99%
“…Currie et al. also measured numerous parameters such as heart rate variability, electrodermal activity and skin temperature in physicians undertaking cardiac endovascular procedures but could not find differences between experience levels [ 31 ]. Hence, mean heart rate seems to be an unreliable predictor, matching the results of our study, where it was not suitable to distinguish between beginners and experts.…”
Section: Discussionmentioning
confidence: 99%